DCMTB: A Virtual Appliance DICOM Toolbox. - Langer S; Charboneau N; French T (Journal of Digital Imaging, 2010)
Medical Imaging has been fortunate to see an avalanche of free and open source software become available in the last several years. Applications have been written to enable image viewing/storage/analysis/processing, DICOM and HL7 message parsing, results aggregation, anonymization, and more. While robust, many of these packages are difficult to install and configure. Our group desired an approach that would mitigate the efforts required to use these packages across different projects. We found such a solution in the context of using virtual machines.